Mir-184 post-transcriptionally regulates SOX7 expression and promotes cell proliferation in human hepatocellular carcinoma. - Geng-Gang Wu; Wen-Hong Li; Wen-Guang He; Nan Jiang; Guang-Xian Zhang; Wei Chen; Hai-Feng Yang; Qi-Long Liu; Yan-Nian Huang; Lei Zhang; Tong Zhang; Xian-Cheng Zeng (PLoS ONE, 2014)
Hepatocellular carcinoma (HCC) is one of the most common human malignancies and the third leading cause of cancer mortality worldwide. The development and progression of HCC is a complicated process, involving the deregulation of multiple genes that are essential to cell biological processes. Recently, microRNAs (miRNAs) have been suggested to be closely associated with tumorigenesis. Our study showed that miR-184 is upregulated in HCC cell lines and tissues. Overexpression of miR-184 in HCC cells increased cell proliferation, tumorigenicity, and cell cycle progression, whereas inhibition of miR-184 reduced cell proliferation, tumorigenicity, and cell cycle progression. Additionally, we identified SOX7 as a direct target of miR-184. Ectopic expression of miR-184 led to downregulation of the SOX7 protein, resulting in upregulation of c-Myc, Cyclin D1, and phosphorylation of Rb. Our findings suggested that miR-184 represents a potential onco-miR and plays an important role in HCC progression by suppressing SOX7 expression.